All that glitters is not gold: curriculum alignment and improving students' test scores - Ghorbani, Mohammad Reza; Abd. Samad, Arshad; Hamzah, Mohd Sahandri Gani; Noordin, Nooreen (University of Zanjan, Iran, 2008)
Due to the centralized educational system in Iran, high school principals have directed English teachers to raise their students' achievement test scores so that they will look good on their school report card. Test scores provide the only benchmark against which the students' progress at school can be measured. Although according to the regulations teachers have to add the oral and written exam scores, and record their combination divided by two on the final report card, they usually rate their students' oral ability based on their performance on the written exam. In this study the report card average score of 47 students in grades one, two, and three at the Iranian senior high school in Kuala Lumpur was compared with that of the newly developed oral and written exam. The report card average score of the three classes was 16.37 out of 20 in comparison to the recent average score of 11.58 out of 20 which is based on the combination of the scores gained from the newly developed oral and written exam. The difference between the report card average and the recent exam average was 4.79 scores, which seems to be due to the exclusion of the oral exam scores by some teachers. The information gained from the focus group interview revealed that most teachers rated their students based on their written performance and neglected the oral exams. This may in part reflect a problem with the instruction in which the teachers teach to the test.